2014
DOI: 10.2147/ijn.s62756
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of nanotized curcumin and demonstration of its antimalarial efficacy

Abstract: Aim The present study was conducted to overcome the disadvantages associated with the poor water solubility and low bioavailability of curcumin by synthesizing nanotized curcumin and demonstrating its efficacy in treating malaria. Materials and methods Nanotized curcumin was prepared by a modified emulsion-diffusion-evaporation method and was characterized by means of transmission electron microscopy, atomic force microscopy, dynamic light scattering, Zetasizer, Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 39 publications
5
30
0
Order By: Relevance
“…However, their poor water solubility at physiological pH, limited absorption, and hence poor bioavailability and chemical instability are major concerns, decreasing their efficacy under in vivo conditions. Biodegradable nanoparticles of curcumin have been developed for antimalarial activity (29). These studies encouraged us to synthesize a polymer-encapsulated formulation of curcumin coated with Eudragit (CNP) for the development of an effective combination oral antileishmanial therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, their poor water solubility at physiological pH, limited absorption, and hence poor bioavailability and chemical instability are major concerns, decreasing their efficacy under in vivo conditions. Biodegradable nanoparticles of curcumin have been developed for antimalarial activity (29). These studies encouraged us to synthesize a polymer-encapsulated formulation of curcumin coated with Eudragit (CNP) for the development of an effective combination oral antileishmanial therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin (1,7‐Bis (4‐hydroxy‐3‐methoxyphenyl) ‐1,6‐heptadiene‐3,5‐Dione) is a natural polyphenolic compound derived from the rhizome of the plant Curcuma longa . It has been used as a traditional medicine since ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, nanotized curcumin was reported to be non-toxic, with a narrow poly dispersity index and improved aqueous dispersibility. The formulation further demonstrated very significant growth inhibition of Plasmodium falciparum and Plasmodium berghei-infected mice [176].…”
Section: Nanosuspensionsmentioning
confidence: 94%